Determination of soil–water characteristic curve variables - Zhai, Qian (2013)
Soil–water characteristic curve (SWCC) contains the fundamental information needed for describing the mechanical behavior of unsaturated soil. Some parameters such as air-entry value, slope at the inflection point, residual water content and residual suction are commonly used to describe the SWCC and other associated properties such as shear strength and permeability. Currently these parameters are determined using the graphical method which can be subjective and time consuming. Equations for determining these parameters are proposed and the relationships between SWCC parameters and fitting parameters are discussed in this paper. These equations can be used for computational analyses to replace the conventional graphical method in providing consistent results.